Efektivitas Kombinasi Dua Obat Antihipertensi Pasien Hipertensi Rawat Jalan RSUD Karanganyar - Tri Wulandari; Anindhita Yudha Cahyaningtyas (Jurnal Farmasi Indonesia, 2021)
The aim of hypertension treatment was to manage and control blood pressure so that the risk of cardiovascular disorders and other complications can be minimized. Blood pressure control can be achieved faster with combination treatment than monotherapy. The use of drugs combination was more effective than inertia therapy and prevented the risk of cardiovascular damage. The purpose of this study was to analyze the effectiveness of combination therapy of 2 drugs that have the highest target achievement for controlling blood pressure in patients with hypertension age ≥ 60 years is <150/90 mm Hg, for patients <60 years is <140/80 mm Hg. The design of this study was retrospective and observational analytic with a cross-sectional approach. Data collection was conducted by reviewing the record of patients. The study samples were outpatients in Karanganyar District Hospital who suffer from hypertension and received the same drug combination therapy for three months successively. The patient's blood pressure was measured during inspection every month. The number of samples in this study was 59 respondents. The results showed that the combination of two antihypertensive drugs most widely used by the CCB + ARB group with achievement target by 92.3% and the lowest achievement target from the combination of diuretic + ARB groups by 20%. The P-value of this research is 0.001 indicated that there were significant differences in the selection of an antihypertensive combination of 2 drugs.